School social work practice, policy, and research - Constable, Robert T.; Massat, Carol Rippey; Kelly, Michael S. (Michael Stokely) 1968- (Oxford University Press, 2022)
"The 9th edition of School Social Work: Practice, Policy and Research marks the further development of school social work as a social work specialization, as well as this venerable textbook itself. American school social work is well into its second century now, and despite ever-present concerns about limited resources, budgets, and school social worker: student ratios, school social work continues to grow, both in the U.S. and internationally. Throughout the U.S. and globally, school social work is becoming increasingly essential to the educational process as families and communities strive to make schools safe and inclusive places for children to learn, to grow, and to flourish. This 9th edition strives to reflect how school social work practice in the third decade of the 21st century effectively impacts academic, behavioral, and social outcomes for youth and the school communities they serve"--